The effects of a high intensity resistance and eccentric strength training program on the performance of handball players - Helena Vila Suarez; Amir Khortabi; Farzad Rezavandzayeric; José María Cancela Carral (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to was to determine the effect of interval and resistance training with a focus on the eccentric phase on the cardiovascular fitness and strength of elite handball players. Thirty handball players were recruited and randomly divided into two groups: an experimental group (age= 20.93±1.70; weight= 78.20±4.58; height= 178.26±3.86) and a control group (age= 21.40±1.76; weight= 77.64±5.92; height= 176.87±4.43). The variables of this study were muscle strength and stamina, power, and cardiovascular fitness. They were assessed by chest press test, push-up, medicine ball throw test, and the Cooper Test, respectively. The training program took place over 12 weeks, with five sessions per week, consisting of two aerobic exercises, and three muscular resistance training exercises focused on the eccentric phase. To analyze the effect of training, a paired sample t-test was employed. The results of this study showed that there were significant pre- to post-test differences in muscle strength (p=0.001), muscle stamina (p=0.001), muscle power (p=0.001), and cardiovascular fitness (p=0.001). The results of the present study indicated that a 12-week eccentric-focused interval and resistance training program improved the strength, stamina, power, and cardiovascular fitness of elite handball players.